(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Seal & Protect is a transparent, adhesive and photopolymerizable solder, it has the effect of covering early exposed dentin areas to prevent or reduce neck wear, prevent tooth decay and treat dentin hypersensitivity. Objective: Evaluation of the effectiveness of treatment of dentin hypersensitivity by Seal & Protect among workers exposed to acids in Lam Thao Super Phosphate and Chemical Joint Stock Company. Methods: Interventional study before-after assessment. Results: The study collected information on 1054 teeth with Moderate, Many and Very sensitive levels in 38 patients who worked in environments exposed to acids.. The results show that the treatment of dentin hypersensitivity with Seal & Protect is very good, easy to perform, very low cost, the effect decreases over time: best right after treatment and in the first 3-6 months, From 6 months onwards, the effect began to decrease much, most teeth returned to the original sensitivity level after 12 months. Teeth with mild sensitivity, when treated will be more effective than teeth with a high degree of sensitivity. Teeth with less wear have a longer treatment effect than teeth with a lot of wear.